2022
DOI: 10.1038/s41598-022-07792-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the hexamerization of SARS-CoV-2 endoribonuclease and modeling of RNA structures bound to the hexamer

Abstract: Non-structural protein 15 (Nsp15) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) forms a homo hexamer and functions as an endoribonuclease. Here, we propose that Nsp15 activity may be inhibited by preventing its hexamerization through drug binding. We first explored the stable conformation of the Nsp15 monomer as the global free energy minimum conformation in the free energy landscape using a combination of parallel cascade selection molecular dynamics (PaCS-MD) and the Markov state model (MSM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 60 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…By contrast, this consistency was observed less frequently in viral RNA recovered after homologous and heterologous reinfection with Omicron variants harboring amino acid substitutions in more diverse regions. Nsp 15 of SARS-CoV-2 functions as an endoribonuclease ( 36 ). Nsp15 and several other SARS-CoV-2 proteins inhibit primary interferon production and interferon signaling and may, thus, interfere with the body's defense against infection ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, this consistency was observed less frequently in viral RNA recovered after homologous and heterologous reinfection with Omicron variants harboring amino acid substitutions in more diverse regions. Nsp 15 of SARS-CoV-2 functions as an endoribonuclease ( 36 ). Nsp15 and several other SARS-CoV-2 proteins inhibit primary interferon production and interferon signaling and may, thus, interfere with the body's defense against infection ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nsp 15 of SARS-CoV-2 functions as an endoribonuclease ( 36 ). Nsp15 and several other SARS-CoV-2 proteins inhibit primary interferon production and interferon signaling and may, thus, interfere with the body's defense against infection ( 36 38 ). Compared with SARS-CoV and other nidoviruses, the Orf10 protein of SARS-CoV-2 is a unique 38-aa protein ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, this consistency was less observed in viral RNA recovered after homologous and heterologous reinfection of Omicron variants, with amino acid substitutions occurring in more diverse regions. Nsp 15 of SARS-CoV-2 functions as an endoribonuclease (36). Nsp15 and several other SARS-CoV-2 proteins inhibit primary interferon production and interferon signaling and thus may interfere with the body's defense against infection (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Nsp 15 of SARS-CoV-2 functions as an endoribonuclease (36). Nsp15 and several other SARS-CoV-2 proteins inhibit primary interferon production and interferon signaling and thus may interfere with the body's defense against infection (36)(37)(38). Compared with SARS-CoV and other nidoviruses, the Orf10 protein of SARS-CoV-2 is a unique 38 aa protein (39).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study identified additional FDA‐approved drugs that can inhibit Nsp15 activity in vitro [ 86 ]. Using high‐resolution structures as the starting point, in silico screening approaches have also identified numerous putative Nsp15 inhibitors [ 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Inhibitors Of Nsp14 and Nsp15mentioning
confidence: 99%